2005
DOI: 10.1386/adch.4.3.189/1
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the teaching of drawing in the digital age: attitudes of senior academics in the United Kingdom to the place of drawing tuition on the design curriculum in higher education

Abstract: A new study has recently been completed investigating current attitudes towards drawing and drawing tuition among senior academics in design education in higher education institutions (HEIs) in the United Kingdom. This study examines some of the main aspects of existing educational practice while also exploring academics' aspirations for ideal drawing tutors and drawing studios. It forms part of an extensive research programme conducted over twenty years on the role of drawing in design practice and its impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 3 publications
0
18
0
Order By: Relevance
“…If students have limited drawing ability, certain software can help them express ideas, develop concepts and sketch on a screen (Schenk, , p. 195). Lastly, it has also been argued that students need to become conversant with the use of digital tools for design (Schenk, , p. 195), and indeed a recent report identified the related skills gap among graduate design students (Montgomery, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…If students have limited drawing ability, certain software can help them express ideas, develop concepts and sketch on a screen (Schenk, , p. 195). Lastly, it has also been argued that students need to become conversant with the use of digital tools for design (Schenk, , p. 195), and indeed a recent report identified the related skills gap among graduate design students (Montgomery, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pamela Schenk has written about attitudes to drawing in the teaching of design, based on a major survey of academics (Schenk 2005(Schenk , 2007. Schenk found that the perceived decline of drawing in the teaching of design disciplines and low drawing ability in students was a matter of serious concern to both design educators and professionals alike (Schenk 2007: 3).…”
Section: What Do Art and Design Students Draw At The Vanda And Why? Abmentioning
confidence: 99%
“…In the primary study, all participants rated the development of drawing ability as "essential" or "important." In comparison, only two-thirds of educators in the second group agreed that the development of drawing ability is "essential" or "important," but most of the group agreed that the value of developing drawing ability in education is crucial for design students (Schenk, 2005). The respondents of her study in 2005, who had teaching experience, admitted both the need for digital software from the early stage of the design process and the ability to quickly draw for ideation, pointing out the limitation of free drawing in digital technology.…”
Section: Need Of Drawing Skills For Interior Design Studentsmentioning
confidence: 97%
“…Pamela Schenk (2005) investigated students' attitude toward the role of drawing in higher education in the United Kingdom by conducting decades of examination (p. 2). This comparison study analyzed present studies and found that there was a gap of more than twenty years between industry and education; the respondents in this study were design practitioners in design studios and educators in art and design.…”
Section: Need Of Drawing Skills For Interior Design Studentsmentioning
confidence: 99%
See 1 more Smart Citation